PERFORMANCE INVESTIGATION OF DESICCANT SYSTEM FOR DEHUMIDIFICATION OF TOPICAL AIR - YAO, MOK WEN (IRC, 2017)
Liquid Desiccant Dehumidification System has been known as an appealing alternative to replace the conventional vapor-compression air conditioner in HVAC applications due to their capability in dealing with high latent heat load in a more energy-efficient manner. A key component in the Liquid Desiccant Dehumidification Systems is the dehumidifier. This dissertation presents the performance investigation of the outlet parameters from a one dimensional mathematical model of a counter-flow liquid desiccant air dehumidifier which is adiabatic. The liquid desiccant, Lithium Chloride (LiCl) is being employed in the dehumidification system. A program with a set of governing equations were being introduced to develop a simple effectiveness model using the engineering equation solver (EES) software. The mathematical solution has come into good agreement with experimental data from various sources with a maximum deviation of approximately 6% in the air moisture removal rate (MRR). The outlet parameters from the dehumidifier are analysed based on the effects of variables such as air relative humidity and temperature and desiccant concentration and temperature. Results have been proven that hot humid air and desiccant temperature and concentration have high influence on the performance of the dehumidifier. As the inlet air relative humidity and inlet air temperature increases, the outlet air relative humidity increases. Whereas as the inlet desiccant solution temperature and inlet desiccant solution concentration increases, the outlet air relative humidity decreases.